Program pengembangan kewirausahaan berorientasi Warung Pendidikan - Ma’rufi Ma’rufi; Muhammad Ilyas; Aswar Anas; Reski Yusrini Islamiah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Entrepreneurship is one of medium to developstudents’ potential, creativity, and innovation. The maincharacteristic of entrepreneurship program in Faculty ofTeaching and Education, Universitas Cokroaminoto Palopo iseducation-based entrepreneurship. Warung Pendidikan orWarpen is one of innovations developed by our faculty, whichsynergizes business matters and education. Warpen coversseveral business such as Warpen Accessories, WarpenTutoring, Warpen Data Analysis, and Warpen Design. Theimplementation of entrepreneurship program in our faculty aretaken from students’ tenants who participated in Students’Entrepreneurship Competition, other entrepreneurshipactivities, and graduates from our faculty who run their ownbusiness. The purpose of this program is to develop andimprove students understanding and skills as entrepreneur andproduce five independent, competitive, and technology-basedbusinesses in our faculty.